Honey bee populations surviving Varroa destructor parasitism in Latin America and their mechanisms of resistance - Guzman-Novoa, Ernesto; Corona, Miguel; Alburaki, Mohamed; Reynaldi, Francisco José; Invernizzi, Ciro; Fernández de Landa, Gregorio; Maggi, Matías (Frontiers in Ecology and Evolution, 2024)
The honey bee (Apis mellifera) parasitic mite, Varroa destructor, is considered one of the main causes of colony losses in European honey bee (EHB) populations around the world. However, some EHB and Africanized honey bee (AHB) populations (derived from the African subspecies A. m. scutellata) that inhabit tropical and subtropical regions of the Americas, have survived varroa mite infestations in the absence of acaricide treatments. It is conceivable to expect that these honey bee populations, which have been subjected to natural selection over decades, would have developed resistance against V. destructor or possess pre-existing adaptations that allow them to survive mite parasitism. Here, we present a comprehensive literature review describing the spread of V. destructor and the honey bee populations occurring in Latin America (LA), and summarize the evidence of resistance of those populations to V. destructor. We also analyze reports describing the potential mechanisms of mite resistance and how they operate in those honey bee populations. Studies of a few EHB, as well as of numerous AHB populations exhibiting resistance to V. destructor in LA, unveil the existence of evolutionary adaptations that restrain V. destructor population growth and provide insight into the current host-parasite relationship. This review supports the notion that selective breeding of local honey bee populations from LA could be a viable strategy to manage varroa mite infestations in colonies.